Experimental investigation of tungsten–nickel–iron alloy, W95Ni3.5Fe1.5, compared to copper monolithic bullets - Abhishek, T.; Sundeep, Dola; Chandrasekhara Sastry, C.; Eswaramoorthy, K. V.; Kesireddy, Gagan Chaitanya; Siva Reddy, Bobbili Veera; Verma, Rakesh Kumar; Salunkhe, Sachin; Cep, Robert; Abouel Nasr, Emad (Frontiers in Mechanical Engineering, 2024)
This study focuses on the production of small armed bullets through the machining of W95Ni3.5Fe1.5 (WNF) alloy and copper monolithic (CM) bullets, setting the groundwork for initial bullet profile-making trials. The investigation covers key machining parameters such as cutting speed and feed, alongside responses including surface roughness, cutting temperature, and hardness, complemented by a comprehensive morphological analysis of the workpiece, chip, and tool used in bullet fabrication. Employing an orthogonal array alongside Multi-Criteria Decision-Making (MCDM) and the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) techniques, this study offers a dual approach for decision-making processes in machining. Our findings reveal that the WNF alloy exhibits significantly lower machining temperatures, ranging from 3.01-27.95%, reduced surface roughness by 24.88-61.85%, and increased microhardness values by 19.45-34% compared to the CM material. The CM bullets, characterized by their inherent softness, demonstrate higher machining temperatures, leading to substantial tool flank wear, which was observed to be 47.53% higher than that of WNF alloy bullets. Furthermore, the study notes a 24.89% reduction in crater tool wear for WNF bullets compared to CM, indicating a superior machining performance. Additionally, a compressive residual stress attenuation of 38.23% in WNF bullet profiles was identified. The manuscript culminates in a ballistic impact analysis conducted through the Finite Element Method (FEM) model in ABACUS, which underscores the potential of WNF alloy bullets in enhancing the ballistic performance and durability of small armed ammunition. These findings underscore the WNF alloy's significant advantages for military and defense applications, providing a solid foundation for future research and development in bullet manufacturing technologies.